Strategi Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) Berbasis Komoditas Getah Karet di Kabupaten Mandailing Natal - Muhammad Ardiansyah; Andy Hakim (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of the Indonesian economy; however, MSMEs based on the rubber (Hevea brasiliensis) commodity in Mandailing Natal Regency remain largely confined to selling unprocessed raw latex with low added value. This study aims to formulate development strategies for rubber-based MSMEs in Mandailing Natal. A qualitative descriptive approach was employed; data were collected through observation, in-depth interviews, and documentation, and were analyzed using the SWOT framework combined with the IFAS-EFAS matrix. The findings reveal that the principal strengths lie in the abundant availability of raw latex and rubber's status as a leading regional commodity, whereas the main weaknesses are low productivity, minimal downstream processing, limited capital, and weak managerial capacity. External opportunities include the national downstream-industry agenda, the recovery of rubber prices, and government financing support, while the threats stem from global price volatility, the EUDR regulation, and land conversion to oil palm. The recommended strategies emphasize strengthening farmer processing-and-marketing units (UPPB), product diversification and downstream processing, capital and digital-marketing facilitation, and rubber-tree rejuvenation, so as to raise the added value and competitiveness of rubber-based MSMEs.